The aetiology and clinical characteristics of cryptococcal infections in Far North Queensland, tropical Australia - Sim, Beatrice Z.; Conway, Luke; Smith, Laura K.; Fairhead, Lee; Der, Yi Shan; Payne, Lara; Binotto, Enzo; Smith, Simon; Hanson, Josh (PLOS ONE, 2022)
Cryptococcal infections are an important cause of morbidity and mortality in tropical Australia. This retrospective audit was conducted to characterise the aetiology, temporospatial epidemiology, and clinical course of 49 cryptococcal infections in Far North Queensland between 1 January 1999 and 31 December 2019. Cryptococcus gattii was identified in 15/32 (47%) in whom it was possible to speciate the organism. Among these 15 patients, 13 (87%) had a rural residential address, 10 (67%) were Indigenous Australians and 11 (73%) presented during the May-November dry season. When compared to the 17 patients with Cryptococcus neoformans infection, patients with C. gattii were less likely to be immunocompromised (0/15 versus 8/17 (47%), p = 0.003). Neurosurgery was necessary in 5/15 C. gattii cases and 3/17 (18%) C. neoformans cases (p = 0.42). Outcomes were generally good with 42/49 (86%) cases—and 14/15 (93%) with C. gattii infection—surviving to hospital discharge. These positive outcomes are likely to be explained by the development of standardised treatment guidelines during the study period, low rates of comorbidity in the patients with C. gattii infection and access to liposomal amphotericin and neurosurgical support in the well-resourced Australian healthcare system.